Birth size, growth trajectory and later cardio-metabolic risk - Cauzzo, Chiara; Chiavaroli, Valentina; Di Valerio, Susanna; Chiarelli, Francesco (Frontiers in Endocrinology, 2023)
There is growing evidence of a strong relationship between intrauterine growth and subsequent development of chronic disease in adult life. Birth size and growth trajectory have been demonstrated to have an impact on cardio-metabolic health, both in childhood and in adult life. Hence, careful observation of the children’s growth pattern, starting from the intrauterine period and the first years of life, should be emphasized to detect the possible onset of cardio-metabolic sequelae. This allows to intervene on them as soon as they are detected, first of all through lifestyle interventions, whose efficacy seems to be higher when they are started early. Recent papers suggests that prematurity may constitute an independent risk factor for the development of cardiovascular disease and metabolic syndrome, regardless of birth weight. The aim of the present review is to summarize the current knowledge about the dynamic relationship between intrauterine and postnatal growth and cardio-metabolic risk, from childhood to adulthood.